2021
DOI: 10.5001/omj.2021.72
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Modified Early Warning Score (MEWS) in the Prognosis of Acute Pancreatitis

Abstract: Objectives: Modified Early Warning Score (MEWS) is a reliable, safe, instant, and inexpensive score for prognosticating patients with acute pancreatitis (AP) due to its ability to reflect ongoing changes of the systemic inflammatory response syndrome associated with AP. Our study sought to determine an optimal MEWS value in predicting severity in AP and determine its accuracy in doing so. Methods: Patients diagnosed with AP and admitted to a single institution were analyzed to determine the value of MEWS in id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Khan et al, conducted a study on the role of MEWS in the prognosis of acute pancreatitis and they found that with 90.8% of specificity and 83.3% of positive predictive value, the highest MEWS value >2 on day one is most accurate in predicting severe acute pancreatitis. Moreover, mean MEWS of >1.2 on day two was the most accurate in predicting severe acute pancreatitis, with a 6.6%, of specificity, 81.2% of sensitivity, 85.9% of negative predictive value, and positive predictive values of 69.8% [15].…”
Section: Discussionmentioning
confidence: 90%
“…Khan et al, conducted a study on the role of MEWS in the prognosis of acute pancreatitis and they found that with 90.8% of specificity and 83.3% of positive predictive value, the highest MEWS value >2 on day one is most accurate in predicting severe acute pancreatitis. Moreover, mean MEWS of >1.2 on day two was the most accurate in predicting severe acute pancreatitis, with a 6.6%, of specificity, 81.2% of sensitivity, 85.9% of negative predictive value, and positive predictive values of 69.8% [15].…”
Section: Discussionmentioning
confidence: 90%
“…Diabetes and hypertension were the main comorbidities. It should be noted that arterial hypertension and infectious processes increase the MEWS score when presenting fever, tachycardia, and hypertension, so it is recommended to use this score to predict the need for specific care [26]. In another study, hypertension was significantly associated with mortality in patients with COVID-19 [10].…”
Section: Discussionmentioning
confidence: 99%
“…It shows that the MEWS score for patients with emergency cardiogenic chest pain can provide a reliable basis for predicting the short-term prognosis. In 2021, Amena Khan et al [15] applied the modified early warning score (MEWS) to the prognosis of acute pancreatitis in order to predict its severity. The results showed that the highest MEWS (hMEWS) score > 2, and the average of all scores on the day (mMEWS) > 1.2 was the most accurate in predicting severe acute pancreatitis, and these findings were more accurate than previous studies.…”
Section: Application Of Mews System In Patient Prognosis Predictionmentioning
confidence: 99%